PERBANDINGAN TINGKAT KEPARAHAN DAN TINGKAT KEBUTUHAN PERAWATAN ORTODONTI MENGGUNAKAN MALALIGNMENT INDEX Tinjauan pada Sekolah Menengah Pertama yang memiliki Unit Kesehatan Sekolah dan Sekolah Menengah Pertama yang Tidak Memiliki UKS - Syada, Akbar Nazarullah; Dwi Kurniawan, Fajar Kusuma; Wibowo, Diana (FKG Unlam, 2017)
ABSTRACT Background: Prevalence of orthodontic treatment needs in Indonesia is still quite high which is around 80%. According to data of Riskesdas South Kalimantan, malocclusion occurrence at the age of 12-15 is 15,6%. Usaha Kesehatan Sekolah (UKS) is a school health unit that serves to improve the health of students, one of its service is about oral health. Maintaining oral health will reduce the occurrence of malocclusion. Purpose: this study was to compare the level of severity of malocclusion and orthodontic treatment needed using Malalignment Index on student in junior high school that have and do not have UKS. Methods: This study was an observational analytic study with cross sectional approach. This study consisted of two groups, junior high school with UKS and without UKS. Result: Level of orthodontic treatment needs in UKS group that did not require treatment was 32 samples, meanwhile 18 samples that need treatment. Level of orthodontic treatment needs in non UKS group that did not require treatment was 8 samples, meanwhile 17 samples that need treatments. Conclution: Chi-square test showed a significant difference between the UKS and non UKS group. Based on research conducted it could be concluded that there was a difference between the level of orthodontic treatment needs between junior high school which have and do not have UKS. Keywords: Malalignment index, orthodontic treatment needs, Usaha Kesehatan Sekolah